The Impact of Task-Based Language Teaching on Nursing Students’ English-Learning Motivation - Widanta, I Made Rai Jaya; Sitawati, Anak Agung Raka; Handayani, Luh Nyoman Chandra; Mandia, I Nyoman; Sumartana, I Made; Aryana, I Nyoman Rajin; Wilang, Jeffrey Dawala (Antitrust law journal, 2024)
This mixed-method study investigated how task-based language teaching (TBLT) implemented in English-for-nursing programmes impacted students’ learning motivation. Specifically, the study explored the motivational patterns that underlie the students’ participation in the learning process, the factors influencing their English-learning motivation, and the aspects of TBLT that positively affected their learning motivation. The data analysed were acquired through questionnaires and interviews. The questionnaire was designed according to the motivational attitude test battery (MATB) by Gardner (2014). The results of the research reveal that intrinsic motivation was the most favourable motivation, followed by instrumental, extrinsic, and integrative motivation. Several factors influenced the students’ English-learning motivation, such as positive teacher-student interpersonal relationships, teacher praise, teacher feedback or strokethe written feedback from teacher, learning tasks and class activities, student curiosity, teaching method, and relatedness. Three aspects of TBLT positively affected student motivation: task activities, autonomous learning and authentic learning motivation, and teachers’ positive facilitation. The findings can help design materials that motivate students, specifically in nursing programmes in which English is not used as a medium of instruction.